2010
DOI: 10.1007/s12177-011-9061-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria impairment correlates with increased sensitivity of aging RPE cells to oxidative stress

Abstract: Impairment of mitochondria function and cellular antioxidant systems are linked to aging and neurodegenerative diseases. In the eye, the retinal pigment epithelium (RPE) is exposed to a highly oxidative environment that contributes to age-related visual dysfunction. Here, we examined changes in mitochondrial function in human RPE cells and sensitivity to oxidative stress with increased chronological age. Primary RPE cells from young (9-20)-, mid-age (48-60)-, and >60 (62-76)-year-old donors were grown to confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 82 publications
2
42
0
Order By: Relevance
“…24 In addition, use of hfRPE cells may have an advantage over adult human RPE cells in that, adult human RPE cells show an age-dependent decline in mitochondrial function and antioxidant potency. 25 In the present study, we found that mini-chaperone peptides derived from aA and aB-crystallins exhibited antiapoptotic properties. Both aA and aB-crystallin mini-chaperone peptides protected RPE from H 2 O 2 -induced cell death and inhibited caspase-3 activation.…”
Section: Discussionsupporting
confidence: 52%
“…24 In addition, use of hfRPE cells may have an advantage over adult human RPE cells in that, adult human RPE cells show an age-dependent decline in mitochondrial function and antioxidant potency. 25 In the present study, we found that mini-chaperone peptides derived from aA and aB-crystallins exhibited antiapoptotic properties. Both aA and aB-crystallin mini-chaperone peptides protected RPE from H 2 O 2 -induced cell death and inhibited caspase-3 activation.…”
Section: Discussionsupporting
confidence: 52%
“…1, NADP-linked processes supporting redox switches are shown in green while representative examples of the broader spectrum of post-translational modifications linking macromolecular structure and function to bioenergetics and metabolism is shown in blue. In this simplified conceptualization, we have omitted details about production of oxidants by mitochondria, which are included within the redox code [6] and extensively studied in terms of pathology and aging [1315]. In addition to pathologic consequences from excess production, evidence is accumulating that mitochondria produce oxidants as signaling molecules that integrate mitochondria-cell functions [1618].…”
Section: Mitochondrial Network and The Redox Codementioning
confidence: 99%
“…Oxidative damage and mitochondrial dysfunction are strongly related to the pathogenesis of various diseases, such as age-related macular degeneration (AMD), Parkinson's disease, heart ischemia/ reperfusion injury, alcoholic hepatitis, diabetes and cardiovascular diseases [10]. Excess reactive oxygen species (ROS) generation and release induces a variety of oxidative stress responses, which further exacerbate mitochondrial dysfunction and result in cell injury and death to accelerate disease progression [11,12].…”
Section: Introductionmentioning
confidence: 99%